A abordagem fenomenológica da antropologia filosófica: pessoa e espírito em Max Scheler - Klaus, Leila Rosibeli (2014)
The work s objective relies mainly on the reading of Scheler s Philosophical Anthropology, to bring up the theme about the problem of man from phenomenological approaches. We attempt to develop Scheler s philosophical perspective through the phenomenological method, which is established mainly by Husserl. The contributions on this philosopher concept of intuition were decisive to the elaboration of Schelerian ethics, but especially to the Philosophical Anthropology. Scheler s concern about the human phenomenon demands a renewed metaphysics. In search of the human being s unity, the Scheleriansmetaphysics together with the phenomenology, rewrite man s essentiality. From that, the man, as person in the world, owns a peculiar structure, namely, the spirit. In turn, this concept grants to Scheler s Philosophical Anthropology the metaphysical leap from the concrete sphere to the transcendental sphere. In order to sustain the thesis concerning the phenomenological method present in the metaphysics of Scheler s Philosophical Anthropology, we start from a historic-conceptual contextualization of Scheler s Philosophical Anthropology. Posteriorly, a more focused analysis will be made of Scheler s more metaphysical thesis, to place the issue of the philosopher s phenomenological affiliation. The main work here analyzed is The Position of Man in the Cosmos (1928). Adjuvant works such as The Ethics and Ideas I, by Husserl, proved importance to the research.